SIMULATION OF HEAT CAPACITIES OF Ti-6Al-4V ALLOY/ NANO SiCP COMPOSITES BASED ON ANSYS - MOHAN, KRISHNA (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
The high strength, low weight ratio and outstanding corrosion resistance inherent to titanium and its alloys has led to a wide and diversified range of successful applications which demand high levels of reliable performance in aerospace, automotive, chemical plant, power generation, oil and gas extraction, sports, and other major industries.Ti-6Al-4V alloy was used as a matrix and SiCp was used as Reinforcement. Ti-6Al-4V alloy with different percentage of (10%, 15%, 20%) nano SiCpComposites were fabricated through Powder mettalurgy route.To cater the needs of various requirements in aspacecraft making, a wide variety of materials are used. Besides, the indigenization efforts and development of new materials for space-use emphasizes the measurement of Cp before their actual use. Specific heat measurement must be also known for design purposes. Thermal calculation using finite element method is employed to solve the temperature dependent specific heat capacity via ANSYS and the three dimensional transient heat transfer problem was solved. In this study, the specific heat capacity of the Ti6Al4V alloy and Ti6Al4V/Nano-SiCp composites in the temperature range of 173K to 648K are determined.